Healthcare Experiences of Underrepresented Lesbian and Bisexual Women: A Focus Group Qualitative Study - Sue LaVaccare; Allison L. Diamant; Julie Friedman; Karen T. Singh; Jessica A. Baker; Tayler A. Rodriguez; Susan R. Cohen; Farina Y. Dary; Janet Pregler; Janet Pregler (Mary Ann Liebert, 2018)
Purpose: To understand the complex healthcare experiences of women identifying as lesbian or bisexual. who are also women of color, veterans, and/or 65 years of age and older. Methods: Inclusion criteria were age 25 or older, Los Angeles County resident, self-identification as a lesbian or bisexual woman, and as an African American, Latina, Asian-Pacific Islander, and/or a veteran. For the age 65 years and older group, participants were eligible regardless of their veteran status or race/ethnicity. Five focus groups were conducted (n=35) and the same questions were asked addressing their comfort interacting with healthcare providers, the provider knowing their sexual orientation, characteristics of a perfect provider, and barriers to care. Structured qualitative analyses were performed. Results: Participants identified concerns that providers often hold to heterosexual cultural norms. Participants varied on preferences for providers of the same race/ethnicity as themselves. Lesbians who are 65 years and older identified legal barriers as major concerns. All groups identified incorrect provider assumptions about sexual orientation and sexual practices as frequently compromising their care. Participants supported the idea of certification for providers skilled in lesbian, gay, bisexual, transgender, and queer (LGBTQ) health, but expressed skepticism that such programs would necessarily result in better care. Conclusion: Healthcare provider trainings need to address the specific concerns and experiences of underrepresented lesbian and bisexual women. Healthcare environments must be transformed to effectively address their needs. More research is needed on the separate healthcare experiences of specific marginalized populations related to their sexual orientation and/or gender identity.